Reconstruction of The Idea Integrating Critical Thinking Based Education On the Junior High School Curriculum - Tapung, Marianus Mantovanny (Universitas Pendidikan Indonesia, 2018)
Indonesia as a developing country that has the level of social problems that high enough, requires education facility is based on the critical thinking. Education which is based on the critical thinking this will form the younger generation that has the capability of knowledge, attitudes, and skills to troubleshoot various social issues, good happens in himself, or that occurred in the community. Many research that gives the impression of the importance of this critical thinking based education so that they can become a consideration for education stakeholders in Indonesia to apply and integrate it in the system of the curriculum, and the teaching material content in the classroom. In order to assist the education stakeholders in implementing and integrating, then there needs to be a reconstruction of ideas and thinking about this critical thinking based education. Now the reconstruction method of ideas, in addition, based onÂ the empirical fact about factual teaching in the age of high school, also based on the study and analysis of a variety of literature closely related to critical thinking based education.